Health-related quality of life in patients with bronchiolitis obliterans - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (WILEY, 2020)
Introduction Bronchiolitis obliterans (BO) is mainly caused by infections and hematopoietic stem cell transplantation (HSCT). This study aimed to investigate the health-related quality of life (HRQOL) of children with BO compared to the healthy children and also to assess the HRQOL according to the etiology. Methods Postinfectious (group 1) and post-HSCT BO (group 2) patients and healthy children were included in the study. HRQOL was assessed by the Short Form-36 (SF-36) and St George's Respiratory Questionnaire (SGRQ). Correlations between demographic and clinical characteristics, pulmonary function tests, high-resolution chest tomography scores, and HRQOL were assessed. Results Thirty-seven postinfectious and post-HSCT BO patients and 34 healthy children were included in the study. Mean age was 13.8 +/- 0.7 years. Mean forced vital capacity and forced expiratory volume(1)were 60.7 +/- 2.7% predicted, and 49.8 +/- 3.1% predicted, respectively. The SF-36 scores were lower in BO patients compared to healthy children (P < .01). Patients with better lung functions had higher SF-36 scores, but lower SGRQ. The number of inhaled therapies, acute exacerbations, hospitalizations were inversely correlated with SF-36. A positive correlation was found between these parameters and total SGRQ scores (r = .507,P = .02;r = .409,P = .12;r = .326,P = .049, respectively). SF-36 scores were better in group 1 for subscales of physical role functioning and social role functioning compared to group 2. (P = .01,P = .01, respectively). Conclusion The HRQOL of patients with BO measured by SF-36 was low compared to healthy children. SF-36 scores were more affected in post-HSCT BO patients. HRQOL of children with chronic lung disease should be taken into consideration in the management of these patients.
Keywords: bronchiolitis obliterans; children; quality of life; VERSUS-HOST-DISEASE; CYSTIC-FIBROSIS; CELL TRANSPLANTATION; CHILDREN